'A Place Full of Whispers': Socializing the Quarry Landscape of the Wadi Hammamat. Issue 4 (15th October 2015) - Bloxam, Elizabeth
Abstract : The wealth of inscriptions at the Wadi Hammamat greywacke quarries (Egyptian Eastern Desert) have made it a key place to pursue enquiries about the social organization of expeditions to procure resources. Analysis of this textual material alone has, however, given us only a partial view of the social milieu that maintained quarrying from the fourth millenniumbc to the fifth centuryad . This article presents a fresh perspective on Egyptian quarrying that aims to balance the more accepted (and persistent) perceptions of overriding state control of these activities with viewpoints gained from recent archaeological survey of the Wadi Hammamat quarries. Practically and theoretically, a holistic approach is taken that contextualizes the textual sources and other elements of the archaeological record within the quarry landscape as a series of material complexes. Cross-cultural and comparative approaches to interpreting the data have enabled both reappraisal and augmentation of the ways in which we understand the social interplay between local and regional kin-groups within notions of state control of these activities. The article argues for the essential roles played by kinship ties and linkages to place, through the continual inscribing of names, as parts of the underlying human narrative that maintained quarrying here for generations.